- #1

I know that we have to use:

m1*v1 + m2*v2 = m1*v1 + m2*v2

the left side is before and the right side is after

m1 = mass of object A

v1 = velocity of object A

m2 = mass of objectB

v2 = velocity of object B

Any help will be appreciated.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter thegreatone09
- Start date

- #1

I know that we have to use:

m1*v1 + m2*v2 = m1*v1 + m2*v2

the left side is before and the right side is after

m1 = mass of object A

v1 = velocity of object A

m2 = mass of objectB

v2 = velocity of object B

Any help will be appreciated.

- #2

wakingrufus

- 14

- 0

m1*v1 + m2*v2 = 0

m1 = mass of the cart

v1 = final velocity of the cart

m2 = mass of a child

v2 = final velocity of a child

you need another equation to solve for 2 variables:

V1 - v2 = 10

solve it for v1:

v1 = 10 + v2

and plug it into your first equation:

120*(10+v2) + (60)(v2) = 0

v2 = -20/3

plug into the second equation: v1 = 10/3

this is just the first step. you have to do it three times, one for each child, using the result from previous one as the initial for the second.

Share:

- Replies
- 15

- Views
- 267

- Last Post

- Replies
- 2

- Views
- 247

- Replies
- 10

- Views
- 323

- Replies
- 4

- Views
- 591

- Replies
- 11

- Views
- 274

- Replies
- 5

- Views
- 542

- Replies
- 11

- Views
- 518

- Replies
- 76

- Views
- 2K

- Replies
- 6

- Views
- 464

- Replies
- 17

- Views
- 1K